BIOM-14. METABOLIC BIOMARKERS OF TERT-TARGETED THERAPY FOR HUMAN GLIOBLASTOMA DETECTED BY MAGNETIC RESONANCE SPECTROSCOPY. (12th November 2021) - Minami, Noriaki; Hong, Donghyun; Stevers, Nicholas; Batsios, Georgios; Gillespie, Anne Marie; Pieper, Russell; Costello, Joseph; Viswanath, Pavithra; Ronen, Sabrina
Abstract: BACKGROUND: TERT promoter mutations that result in TERT expression are observed in over 80% of GBM. Moreover, the upstream transcription factor GABPB1 was recently identified as an ideal therapeutic target for tumors with TERT promoter mutations. In that context, non-invasive reliable biomarkers that can help detect TERT expression are needed. The aim of this research was to assess the value of MRS-detectable metabolic changes as biomarkers of TERT expression and TERT-targeted therapy in GBM. METHODS: Genetically engineered GBM cells (NHARas/TERT) treated with TERT siRNA were compared to siCtrl-treated cells, and stable TERT and GABPB1 knock down GBM cells (U251, GBM1) were compared to shCtrl. 1 H-MRS and 13 C-MRS metabolic data was acquired from cell extracts using a Bruker 500MHz scanner. Hyperpolarized MRS studies of live cells used a HyperSense DNP polarizer and data was acquired using a Varian 500MHz scanner. Spectra were analyzed using Mnova and Matlab software. Multivariate data analysis was performed using SIMCA software. RESULTS: Unbiased PCA analysis of 1 H-MRS metabolic data showed separation of TERT or GABPB1 knock down and control cells. VIP predictive scores revealed that lactate and GSH were the top altered metabolites with a significant drop observed in both metabolites in every model following TERT silencing. Consistent with the reduction in GSH, spectrophotometric assays showed a significant drop in NADPH and NADH. 2- 13 C glucose flux analysis revealed that both glycolysis and PPP-related metabolites were reduced in TERT knock down cells. Hyperpolarized [1- 13 C]-pyruvate flux to lactate was also reduced, confirming that the glycolytic pathway was altered following TERT knock down. CONCLUSION: 1 H MRS-detectable lactate and GSH, combined with hyperpolarized 13 C MRS-detectable metabolic fluxes, could serve as metabolic biomarkers of TERT-targeted therapy for human GBM with TERT promoter mutations. These biomarkers could be translated to the clinical, improve the monitoring of GBM patients and advance precision medicine.